EFEKTIVITAS PEMBERIAN MODUL TERHADAP TINGKAT PENGETAHUAN TENTANG PUBERTAS - Jalanti, Elyzabeth Sari; Wahyuningsih, Heni Puji; Setiyawati, Nanik (Jurnal Kesehatan Ibu dan Anak, 2014)
Puberty is a period of transition towards teenage children who are at risk because some teenagers difficulty in dealing with the changes, so susceptible to free sex, sexual harassment, and IMS. Knowledgeable Effectiveness module providing the level of knowledge about puberty in Class VII students of SMP Negeri 4 Depok Sleman. Experiments with a pretest-posttest with control group design. Sample using purposive sampling techniques that students of class VII SMP N 4 and 5, respectively Depok 38 students who have not puberty. Instrument using the questionnaire of 32 questions. Do granting puberty modules in the experimental group, while the control group was given no treatment. Data analysis by paired t-test control test and independent t-test. Results of students' knowledge gaps with pretest and posttest experimental 15.8% to 76.3%, while the control 10.5% to 5.3%. The experimental group had a sig 0,000 and 0,001 control group, no difference between the level of students' knowledge before and after treatment. There are differences in the mean value of experimentation group and the control group 20.9474 21.8684. 0,000 sig, there are differences in the mean increase in knowledge of the experimental group and the control group -0.6842 3.6842. The difference in mean value 4.36842 improvement. There are different levels of knowledge between the given modules and modules of puberty was not given to increase knowledge about puberty in class VII student of SMP Negeri 4 Depok Sleman.